2022
DOI: 10.3389/fmicb.2022.840846
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Patients With Diarrhea for Having Clostridioides (Clostridium) difficile Infection

Abstract: Nosocomial infections with Clostridioides (Clostridium) difficile have become an emergent health threat. We sought to define risk factors for a C. difficile infection (CDI) beyond the widely known ones, such as antibiotic use and prior hospital stay. We therefore focused on a group of patients with diarrhea in order to identify risk factors for C. difficile infection among this symptomatic cohort. A total of 121 hospitalized patients from Seesen/Germany with diarrhea were included who submitted a stool sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We hypothesized that this association between height, diversity, and CDI could be influenced by diet, as prior research has shown that increasing consumption of a larger variety of plants is positively associated with gut microbiome alpha diversity, and more specifically, eating fewer vegetables has been found to be a risk factor for CDI [ 69 , 70 ]. We partitioned our analysis by self-reported vegetable consumption, looking at differences in height between those with or without a history of CDI in high and low vegetable consumption groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that this association between height, diversity, and CDI could be influenced by diet, as prior research has shown that increasing consumption of a larger variety of plants is positively associated with gut microbiome alpha diversity, and more specifically, eating fewer vegetables has been found to be a risk factor for CDI [ 69 , 70 ]. We partitioned our analysis by self-reported vegetable consumption, looking at differences in height between those with or without a history of CDI in high and low vegetable consumption groups.…”
Section: Resultsmentioning
confidence: 99%
“…In a prior study, CDI patients tended to report consuming fewer vegetables than individuals without CDI, highlighting the role of diet in CDI prevention [ 69 ]. Dietary plant intake has a stronger positive influence over diversity than almost any other lifestyle factor in human cohorts [ 9 , 13 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most patients with IBD were younger than 60 years old and the comorbidity burden rate was very low, which is different from the general CDI population. 34 , 35 , 36 In the general population, clindamycin, extended‐spectrum cephalosporins and fluoroquinolones have been reported to be associated with CDI. 35 Similar antibiotics were prescribed in 21.5% of IBD cases in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is that community-based CDI is incrementally on the rise, further exacerbating the disease burden associated with CDI [ 10 ]. Antibiotic use [ 11 ], old age [ 12 ], gastric acid inhibitors [ 13 ], and hospitalization [ 14 ] are the critical risk factors for the development of such infections.…”
Section: Introductionmentioning
confidence: 99%